2022
DOI: 10.3389/fmicb.2022.902181
|View full text |Cite
|
Sign up to set email alerts
|

Outer Membrane Vesicles as Mediators of Plant–Bacterial Interactions

Abstract: Plants have co-evolved with diverse microorganisms that have developed different mechanisms of direct and indirect interactions with their host. Recently, greater attention has been paid to a direct “message” delivery pathway from bacteria to plants, mediated by the outer membrane vesicles (OMVs). OMVs produced by Gram-negative bacteria play significant roles in multiple interactions with other bacteria within the same community, the environment, and colonized hosts. The combined forces of innovative technolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 110 publications
0
3
0
1
Order By: Relevance
“…Several studies reported that the metabolites adenosine, acetylcholine, serotonin, palmitoleic acid, and others could induce larval settlement and metamorphosis of a variety of aquatic invertebrates, such as mussels, barnacle cyprids, and sea urchins (Kitamura, 1993 ; Faimali et al, 2003 ; Glebov et al, 2014 ; He et al, 2021 ). Numerous chemical cues carried by bacterial OMVs suggested their possible functions in interactions between bacteria and their animal host (Biller et al, 2014 ; Rudnicka et al, 2022 ). Furthermore, it was also verified that SP-7-OMVs, which carried signal molecules such as glycine, glutamic acid, and gamma-aminobutyric acid, could overcome cell barriers to aid in the growth and development of the host.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that the metabolites adenosine, acetylcholine, serotonin, palmitoleic acid, and others could induce larval settlement and metamorphosis of a variety of aquatic invertebrates, such as mussels, barnacle cyprids, and sea urchins (Kitamura, 1993 ; Faimali et al, 2003 ; Glebov et al, 2014 ; He et al, 2021 ). Numerous chemical cues carried by bacterial OMVs suggested their possible functions in interactions between bacteria and their animal host (Biller et al, 2014 ; Rudnicka et al, 2022 ). Furthermore, it was also verified that SP-7-OMVs, which carried signal molecules such as glycine, glutamic acid, and gamma-aminobutyric acid, could overcome cell barriers to aid in the growth and development of the host.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, enzymes contained in OMVs from P. putida have been shown to help to degrade lignin-derived aromatic compounds from plants. Katsir and Bahar and Rudnicka et al review the relationship between OMVs and plants more thoroughly elsewhere. , …”
Section: Extracellular Vesicles As Functional Colloids In the Environ...mentioning
confidence: 99%
“…3 OMVs and plants more thoroughly elsewhere. 118,119 Besides plant−microbe interactions in agricultural systems, attention has been directed toward understanding other roles for EVs in soil and sediment. EVs from both Gram-negative (Mycobacterium tuberculosis) and Gram-positive (Dietzia sp.…”
Section: Functions Of Evs Asmentioning
confidence: 99%
“…Tại các tế bào có chất ức chế hoặc tế bào chết, một số vi khuẩn có thể tạo cấu trúc màng bao bọc. Những màng này giúp vi khuẩn tự bảo vệ khỏi những áp lực như thiếu chất dinh dưỡng hoặc sự hiện diện của các chất có hại trong tế bào (Rudnicka et al, 2022). Hình ảnh cấu trúc giải phẫu từ Hình 1 và Hình 2, có thể cho thấy con đường vi sinh vật tiếp cận với cơ quan sinh dưỡng của cây Xuyên tâm liên bắt đầu bằng xâm nhiễm qua biểu bì, định khu bên trong tế bào và di chuyển qua lại giữa các mô có vách bằng cellulose (nhu mô, giao mô và mô libe).…”
Section: Hình 1 Cấu Trúc Giải Phẫu Các Cơ Quan Sinh Dưỡng Của Cây Xuy...unclassified